ANIMATED VIDEO-BASED LEARNING ON THE FORES AND PROPERTIES OF OBJECTS FOR CLASS II SD NEGERI 2 CALANG - Sri Sumida; Siti Mayang Sari; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The use of animated videos in education has become an integral part of the learning process, especially at the elementary school level. This article explores the contribution and positive impact of using animated videos in the context of early childhood learning. Focusing on its benefits in strengthening conceptual understanding, providing a fun visual learning experience, and supporting the development of students' creative and collaborative skills. Through engaging visual depictions and personalization of the learning experience, this approach enriches traditional methods by creating a more interactive learning environment and stimulating students' critical thinking. By integrating animated videos in the elementary school curriculum, we pave the way to create more engaging, effective and relevant learning for future generations. In this context, the use of visuals in the form of animation encourages student involvement in the learning process, strengthens memory, and helps them understand physical and natural concepts more thoroughly. By introducing animated videos as part of learning about the shapes and properties of objects, this article highlights the important role of technology in providing a more dynamic and fun teaching method for elementary school students.